Grand Canyon / Cari Meister. - Meister, Cari. (Edina, Minn. : ABDO Pub. Co., 2000)
Describes the history, geographic features, and plant and animal life of the natural wonder known as the Grand Canyon and the activities of visitors to Grand Canyon National Park.
Includes index.
13
Keywords: Grand Canyon (Ariz.) -- Juvenile literature; Grand Canyon (Ariz.); Grand Canyon National Park (Ariz.); National parks and reserves